2015
DOI: 10.1186/s13048-015-0149-z
|View full text |Cite
|
Sign up to set email alerts
|

OvAge: a new methodology to quantify ovarian reserve combining clinical, biochemical and 3D-ultrasonographic parameters

Abstract: BackgroundIn the last decade, both endocrine and ultrasound data have been tested to verify their usefulness for assessing ovarian reserve, but the ideal marker does not yet exist. The purpose of this study was to find, if any, a statistical advanced model able to identify a simple, easy to understand and intuitive modality for defining ovarian age by combining clinical, biochemical and 3D-ultrasonographic data.MethodsThis is a population-based observational study. From January 2012 to March 2014, we enrolled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 23 publications
1
25
0
1
Order By: Relevance
“…The main outcomes were differences between control group (BPS) and intervention group (BTS) regarding ovarian reserve parameters including AMH, FSH, AFC, PSV, VI, FI, VFI as well as calculated ovarian age (OvAge/ year) from the following formula OVAge = 48.05 -3.14 AMH + 0.07 FSH -0.77 AFC -0.11 FI + 0.25 VI + 0.1 AMH x AFC + 0.02 FSH x AFC (24,25) at one year after performed tubal sterilizing procedure at time of cesarean delivery (CD). The subsidiary outcomes were related to operational feasibility as well as surgical consequences of tubal sterilizing procedures including operative time as well as total and tubal procedure related estimated blood loss, blood transfusion and related organs injuries.…”
Section: Methodsmentioning
confidence: 99%
“…The main outcomes were differences between control group (BPS) and intervention group (BTS) regarding ovarian reserve parameters including AMH, FSH, AFC, PSV, VI, FI, VFI as well as calculated ovarian age (OvAge/ year) from the following formula OVAge = 48.05 -3.14 AMH + 0.07 FSH -0.77 AFC -0.11 FI + 0.25 VI + 0.1 AMH x AFC + 0.02 FSH x AFC (24,25) at one year after performed tubal sterilizing procedure at time of cesarean delivery (CD). The subsidiary outcomes were related to operational feasibility as well as surgical consequences of tubal sterilizing procedures including operative time as well as total and tubal procedure related estimated blood loss, blood transfusion and related organs injuries.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, recently, some authors validated a new mathematical tool to predict ovarian age, using some hormonal and ultrasonographic parameters. Using multiplanar and inversion mode 3D, they showed that AFC is a reliable marker for ovarian reserve, but did not compared to 2D; in addition, the sample was composed mainly by fertile patients [6]. …”
Section: Introductionmentioning
confidence: 99%
“…Scientists and clinicians are joining forces in a synergistic effort to improve the effectiveness of infertility care by introducing novel therapeutic protocols for the purpose of customising care and improving cost-effectiveness, for example, by adopting New frontiers in human assisted reproduction -from research to clinical practice: Several considerations (Review) different formulations of gonadotropins according to different cohorts of patients and the IVF setting (6,7), testing novel drugs (for example, introducing recombinant luteinising hormone) and formulations (e.g. long-acting gonadotropins), and searching for novel markers for estimating biological age (8,9), and novel nomograms to optimise the yield of a controlled ovarian hyper-stimulation cycle. On the other hand, political, social and health institutions are doing little to educate young women with respect to disinformation and to increase their awareness regarding age as the predominant factor that contributes towards the decline in fertility.…”
Section: Introductionmentioning
confidence: 99%